The influence of S. frutescens on adrenal cytochrome P450 11B-hydroxylase - Sergeant, Catherine Anne (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Biochemistry))--University of Stellenbosch, 2009.